The Influence of Readiness to Use Technology and Creativity on Task Performance: Perspectives from the Fashion Creative Industry in Bandung City - Iwan Sidharta; Asep Rochyadi Suherman; Haritsatun Najwa; Merry Pramashela; Riska Yuni Astuti (Jurnal Computech & Bisnis (e-journal), 2023)
It cannot be denied that technology is one of the factors driving business competition. Thus, technological preparation is one of the determining factors in winning business competition. In the creative industry sector, fashion requires a high level of creativity. So, it is necessary to prepare employees to use technology that can increase creativity, which has implications for employee work; this study focuses on predicting the construct of technological readiness that impacts employee creativity and its implications for completing employee assignments in the fashion industry sector in Bandung. The 243 respondents involved with the structural equation-PLS model prediction approach showed different results where the overall construct of technological readiness can increase employee creativity and have implications for performance. The research results indicate that efforts are needed to select innovative, easy, comfortable, and safe technology. So it can speed up work productivity. The results of this research cover the gap in previous research, showing that yet to be research has examined the effect of technological readiness and creativity on increasing employee work in the fashion creative industry.